Quo Vadis Urgensi Politik Hukum Siber Indonesia dalam Reaktualisasi Peran TNI untuk Penguatan Keamanan Maritim - Muhammad Charles Nur Oktawijaya; Laila, Binti Lailatul Masruroh (JIMLY LEGAL YUSTISIA JOURNAL, 2024)
Indonesia, as an archipelagic country, faces serious challenges in maintaining the sustainability of coastal and marine environments that are increasingly threatened by pollution and damage to maritime ecosystems. This study analyzes legal politics in sustainable maritime development, with a focus on legal protection for marine pollution reporters. The method used is qualitative descriptive research with a normative and empirical legal approach, which examines positive legal instruments and their implementation. The results of the study show that although there are regulations governing the rights of reporters, such as in Law No. 27/2007 junto Law No. 6/2023, legal protection for reporters is still weak and not comprehensive. Cases of criminalization of environmental activists show that public participation in reporting marine pollution is hampered by legal and social threats. Therefore, a progressive legal political reformulation is needed that is responsive to factual conditions. One solution is a technology-based reporting system, Seacurity, which prioritizes anonymity, digital security, and transparency of law enforcement. The implementation of Seacurity is expected to increase public participation in monitoring the maritime environment safely and efficiently, and support the achievement of the Sustainable Development Goals (SDG 14).